KETERAMPILAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH SEGIEMPAT DITINJAU DARI SELF-CONFIDENCE - Angelica Ona Ernitasari; Susanto Susanto; Lela Nur Safrida; Sunardi Sunardi; Ervin Oktavianingtyas (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study was to describe the creative thinking skills of class VIII SMPN 11 Jember students by paying attention to students' self-confidence in solving rectangular problems. The type of research is descriptive qualitative research. The research subjects were 30 students. Methods of collecting data using questionnaires, tests, and interviews. The instruments used are self-confidence questionnaires, creative thinking skills test questions, and interview guidelines. Students' creative thinking skills are needed when learning activities. Creative thinking skills are skills in creating a new idea that can be combined into something new and relatively different from previously existing ideas and can be used to solve a problem with the indicators used, namely fluency, flexibility, originality, and elaboration. Students' self-confidence is measured by paying attention to indicators, namely believing in their own abilities, acting positively in dealing with problems, acting independently in making decisions, having a positive self-concept, and being brave in expressing opinions. The data analysis method used is the questionnaire method, the test method, and the interview method. The results obtained from this study are students with low self-confidence have low achievement on all indicators of creative thinking skills, students with moderate self-confidence have high achievement on indicators of fluency and flexibility indicators. Students with high self-confidence have high achievement on all indicators of creative thinking skills.